Interpretasi Struktur Geologi Regional Pulau Bangka Berdasarkan Citra Shuttle Radar Topography Mission (SRTM) - Franto Franto (PROMINE, 2015)
This paper aims to present the regional geological information related to geologic structure on the Bangka island. In this paper the processing done digitally on the image of SRTM (Shuttle Radar Topography Mission) by combining the value of azimuth and altitude in order to obtain the number of alignment able delineated and recognizable become more by incorporating N0oE, N45oE, N90oE and N315oE artificial lighting as well as the value of the slope of the sun at 45o. Based on the interpretation of the results obtained Hillshade and rose diagram direction relative straightness dominant northwest-southeast trending interpreted as a manifestation of the direction stance layers, but it also contained lineament trending northeast-southwest according Margono et al. (1995) a rock folds covering Tanjung Genting Formation and Ranggam Formation, large tilt between 18o-75o and showed great intensity and there is tectonic lineament trending north-south, according to Mangga and Djamal (1994) was a fault and the fault is in the phase of the youngest as well as the fracturing horizontal cut of older faults (Crow , 2005). Straightness morphological pattern of spread and intensity level of tectonic deformation by the force in the research area is obtained by calculating the count lineament density based Geographic Information System with ArcGIS 9.3 in order to obtain density interval straightness into three classes, 0-28.72503662 km / km2 (low), 28.72503663- 57.45007324 km / km2 (medium) and 57.45007325-86.17510986 km / km2 (height) The higher the intensity, the area is assumed to be much deformed and most likely close to the structure geology.